ANALISIS SIYASAH SYAR'IYAH TERHADAP DINAMIKA KEADILAN DAN DUALITAS PENEGAKAN HUKUM DALAM SERIAL ANIME ONE PIECE - Malisa Utami; Arif Sugitanata (JURNAL DARUSSALAM: Pemikiran Hukum Tata Negara dan Perbandingan Mazhab, 2024)
This study conducts an in-depth analysis of the representation of justice systems and the duality of law enforcement as depicted in the popular manga and anime series "One Piece" by Eiichiro Oda. Employing a literature review with Siyasah Syar'iyah theory as the theoretical framework, this research explores how concepts within Siyasah Syar'iyah can be applied to understand the complex justice system presented in this fictional world. The research is divided into two main sections: firstly, examining the representation of the justice system in "One Piece," where law is applied across various characters and situations, highlighting conflicts and compromises between personal morality and the prevailing law. Secondly, the study integrates the perspective of Siyasah Syar'iyah to analyze how these principles are applicable in the context of law and justice within the narrative. The findings indicate that, although "One Piece" is a work of fiction, its representation of the justice system and the duality of law enforcement reflects relevant justice issues in actual society. The Navy and the World Government in "One Piece" often implement actions that are absolute and monolithic, demonstrating a tendency to disregard fair legal processes and human rights. This practice conflicts with the principles of Siyasah Syar'iyah, which emphasize justice, transparency, and accountability. The study also highlights how power and social status can influence the interpretation and application of justice, as represented by Tenryuubito and Yonko, showing disparities in social and legal justice. Therefore, "One Piece" not only entertains but also provides a platform for critical discussions on justice and law enforcement, enabling reflection on real-world justice practices. This research adds a new dimension to the study of law and justice by integrating the principles of Siyasah Syar'iyah. It enriches the literature on interdisciplinary analysis between law, pop culture, and Islamic studies.